Relationships matter! — Utilising ethics of care to understand transitions in the lives of adults with severe intellectual disabilities. (23rd March 2021) - Jacobs, Paula; Quayle, Ethel; Wilkinson, Heather; MacMahon, Ken
Accessible summary: People with severe and profound intellectual disabilities need others to support them in most areas of their life. It can be difficult to communicate with people about change and transitions have been identified as an area of concern. As part of this research, we spent time with six adults with severe and profound intellectual disabilities. We talked to their families and professionals about their transitions and how they were involved in decisions that were made. Relationships people had with family members and key staff facilitated their engagement and experiences of the world. Our findings show that it is important that those who know the person well are closely involved in the planning of transitions. There should be a greater focus on maintaining the relationships that people have so that we can build bridges between settings and improve transitions for people with intellectual disabilities. Abstract: Background: Within the current literature, there is a focus on early transition experiences, such as people's school years, while adulthood remains a lesser researched chapter in the lives of people with intellectual disabilities. Furthermore, most studies focus on those with mild or moderate intellectual disabilities and people with severe or profound intellectual disabilities are often excluded from research. Methods: This article explores the transition journeys of six adults with severe intellectual disabilities, including transitions from school to adult services and moving out of the family home. Data collection involved observations, document reviews and interviews with families and professionals in Scotland. Taking an ethics of care perspective, our focus was to explore in how far each person had people in their lives able to listen to them and if, in turn, those close to them were listened to during times of transition. Findings: Our findings demonstrate that transitions are complex processes that occur across different systems. Additionally, our findings emphasise the importance to consider relationships that are available to people within their adult lives when planning and supporting transitions. Combining interviews with observations helped us to see how the six adults showed agency and were communicating their preferences through the relationships they had with people within their immediate environment. Conclusions: The need to reconceptualise participation from a relational and interdependent perspective is stressed to facilitate the involvement of people with severe intellectual disabilities within decision‐making processes.